Columella reconstruction with an inferiorly-based philtral advancement flap in a cocaine abuser - Davide Di Santo; Matteo Trimarchi; Andrea Galli; Mario Bussi (Indian Journal of Plastic Surgery)
Nasal columella defects can significantly impair aesthetic appearance. Columella reconstruction can be very challenging for surgeons, especially if due to cocaine abuse. The case of a 32-year-old male patient with subtotal columellar necrosis secondary to cocaine abuse is presented. An inferiorly based philtral advancement flap was performed to cover the defect. Aesthetic outcome was the primary goal of surgery. Reconstruction led to good aesthetic and functional results.